2015
DOI: 10.1007/s11746-015-2667-7
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Equation for Estimation of Kinematic Viscosity of Fatty Acid Methyl Esters and Biodiesel

Abstract: proposed model would be good for estimation of viscosity of biodiesel containing normal fatty acids, generally found in biodiesel feed stocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 27 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…The Bias and AAD were not very different from those obtained from Eq. 10 for kinematic viscosity [16]. Accordingly, it might be concluded that the six numeric coefficients of Eq.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The Bias and AAD were not very different from those obtained from Eq. 10 for kinematic viscosity [16]. Accordingly, it might be concluded that the six numeric coefficients of Eq.…”
Section: Resultsmentioning
confidence: 95%
“…6 or 9 are generally determined by multiple linear regressions against the experimental values. The values given by Phankosol et al [4,16] for kinematic viscosity and density are shown in Eqs. 10 and 11, Equation 12 is obtained by combining Eqs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many physical properties of FAME and biodiesel were correlated to their z and n d via GEA method. These properties were molecular compressibility ( k m ) (Krisanangkura et al, 2019), isentropic compressibility ( k s ) (Krisanangkura et al, 2018); density (ρ) (Phankosol et al, 2014a), surface tension (Phankosol et al, 2014b), kinematic viscosity (μ) (Phankosol et al, 2015), dynamic viscosity (η) (Krisnangkura et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the correlation was successfully applied in predicting four binary biodiesel blends (Chavarria‐Hernandez and Pacheco‐Catalán, ). Phankosol et al proposed a correlation for estimation of kinematic viscosity of FAME and biodiesel as a function of the number of carbon atoms, the number of double bonds, and temperature (Phankosol et al, ). Meng et al used artificial neural networks in predicting the viscosity of biodiesel as a function of the viscosity of pure FAME.…”
Section: Introductionmentioning
confidence: 99%